Urbanismo, corrupción y delincuencia organizada: Conclusiones y recomendaciones - Diez Ripollés, José Luis; Gómez-Cespedes, Alejandra; Prieto del Pino, Ana María; Stangeland, Per; Vera Jurado, Diego (Boletín Criminológico, 2003)
Urbanismo, corrupción y delincuencia organizada: Conclusiones y recomendaciones